Analisis Kebutuhan terhadap Pengembangan Media Pembelajaran Berbasis Virtual Field Trips dalam Pembelajaran IPA di Jenjang Sekolah Dasar - Heni Yunilda Hasibuan; Vina Oktiarina; Mulki Siti Hajar Rezaini; Lukman Nulhakim; Yayat Ruhiat (Postgraduate, University of Mataram, 2023)
Since the COVID-19 pandemic, various technology-based learning media have been developed, including various museums and institutions' availability of Virtual Field Trips (VFT). This can be considered an innovation in science learning that is expected to enhance students' cognitive and affective abilities. This research aims to analyze the need for developing VFT-based learning media in science education at the elementary school level. The study adopts a qualitative approach by collecting quantitative and qualitative data from questionnaire surveys. The respondents, consisting of 33 elementary school teachers from various regions in Indonesia, are familiar with using electronic devices and internet connectivity to support technology-based learning, which is already widely implemented in their science classes. Moreover, elementary school teachers are accustomed to using technology-based learning media in science education. However, there is a need to develop technology-based learning media, particularly Virtual Field Trips (VFT), in science education at the elementary school level as an innovative approach to teaching. Therefore, further research on developing VFT-based learning media in science education at the elementary school level is warranted.